2022
DOI: 10.1002/eqe.3725
|View full text |Cite
|
Sign up to set email alerts
|

Reduced‐order models for the seismic assessment of plan‐irregular low‐rise frame buildings

Abstract: A procedure is presented for deriving low‐complexity structural models to predict the global response of asymmetric‐plan low‐rise frame buildings for purposes of class‐level assessment. As a compromise between employing a full‐scale multi‐degree‐of‐freedom structural model versus an equivalent single‐degree‐of‐freedom one, the challenge is to create an idealized 3D structure with few degrees‐of‐freedom that can match the inelastic response of a building for which full knowledge of geometrical and mechanical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…For example, Kazantzi and Vamvatiskos showed that Sa avg can reduce bias in vulnerability assessment of building classes, particularly if calculated for class-average second and elongated first modes [82]. Similarly, Ruggieri et al showed that Sa avg can be used for fragility analysis of an RC building stock with different topological parameters or plan-irregular low-rise frames [83,84].…”
Section: Scalar Imsmentioning
confidence: 99%
“…For example, Kazantzi and Vamvatiskos showed that Sa avg can reduce bias in vulnerability assessment of building classes, particularly if calculated for class-average second and elongated first modes [82]. Similarly, Ruggieri et al showed that Sa avg can be used for fragility analysis of an RC building stock with different topological parameters or plan-irregular low-rise frames [83,84].…”
Section: Scalar Imsmentioning
confidence: 99%
“…For example, Raheem et al(Abdel Raheem et al, 2018) analyzed the seismic response of L-shaped irregular buildings showing that buildings with irregular planar layouts have worse seismic performance compared to regular buildings; In the Wenchuan earthquake of 2008, the external-corridor type buildings widely used in classroom buildings, dormitories, and office buildings were severely damaged; In the 1985 Mexico earthquake, about 50% of buildings were damaged because of the torsional effect generated by the irregular arrangement of lateral load-resisting members directly or indirectly (Chandler, 1986;Meli and Rosenblueth, 1986) Therefore, considering the irregularity characteristic of buildings in regional seismic damage simulation has significant engineering values. Because of the high number of buildings in regions, a spatial simplified model is a feasible method to moderately consider the lateral-torsional coupling effect of irregular buildings (Ruggieri et al, 2022). Blasonea et al (Blasone et al, 2022) proposed a simplified spring model to simulate irregular RC frames, which use two perpendicular lateral shear springs to simulate the mechanical behavior of each column and the connected beams.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the load amplification factors in the two horizontal directions were suggested and differed significantly from those of the European code. Ruggieri et al [24] presented a procedure for low-complexity structural models to predict the global response of asymmetric-plan low-rise buildings. This procedure created an idealized 3D structure with a few degrees of freedom compared with a full-scale multi-degree-of-freedom structural model, and the proposed structure can match the inelastic response of a building.…”
Section: Introductionmentioning
confidence: 99%